The Position of Women in the Dynamics of Modern Tafsir: Study of Tafsir Al-Tahrir wa al-Tanwir by Muhammad Tahir Ibn 'Ashur - Ibrahim, Sulaiman; Khaerul Asfar (Pascasarjana IAIN Sultan Amai Gorontalo, 2023)
This paper aims to explore the position of women in the dynamics of modern tafsir study on Tafsir Al-Tahrir wa al-Tanwir by Muhammad Tahir Ibn 'Ashur. Tafsir is a representative of modern tafsir that is widely used as literature to discuss contemporary issues. The research uses literature review with a qualitative approach and accompanied by discourse analysis. The results showed that the position of women in the Qur'an according to Ibn 'Assyria does not deny the difference with men, and this is aimed at aspects of their respective roles in the order of life. The difference as illustrated by the Qur'an is in the form of the difference between night and day, the existence of both of which becomes a unity of Allah's decrees and provisions or sunnatullah (created this universe is always paired with each other). The work of women in the public world is no longer a rare sight. The opening of fields and job opportunities that are no longer strict with gender criteria, progress in the field of education, poverty experienced by most families, are all factors that are very instrumental in increasing taking part in the public sphere. Interestingly, the success of women in carrying out their duties is not inferior to that of men, proving that success in the public sphere is not related to gender criteria.